EKSPLOITASI PEREMPUAN DALAM PERIKLANAN MENURUT PANDANGAN ISLAM - Asmaunizar Asmaunizar (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2015)
Women occupy a secondary position appear in television journalism mainly through advertising channels. The number of male employees who manage television much more than female employees. Even if there are no female employees hold on important role that determines the publication or broadcasting policies, presentation of news, features and opinion. In view of the commercial advertisement male hegemony will automatically make women and their sexual attractiveness as an object so that exploitation is difficult to avoid. The deviation of advertising such as showing women in skimpy outfits, it's beyond the basic concept and management of real advertising. It was because of the pursuit of profit alone as a result of competition existing media in improving the economic enterprise. In accordance with its function, the media is able to provide educational, entertaining and affecting people's lives. In accordance with its function, the media is able to provide educational, entertaining and affecting people's lives. Media as a guard or guards truth, television perform its functions to the social control of the errors that occur in the community. Based on the study of Islam that advertising as a means of delivering information can spread the message of the form of propaganda for any positive information. The information such as information on trade, education, health and information broadcasting Islamic religion and so forth. Of the facts shows that the global information flows almost entirely unbalanced , more coming from the western culture to Islamic culture , including in terms of advertising. Keyword: exploitation,Women, advertisement, Islam